Patrician brotherhood : masculinities, politics and nation building in Singapore 1950s-1970s - Locham, Sharanjeet Kaur (2019)
Much has been written on Singapore’s political history detailing aspects of the political ascendency of the People’s Action Party since self-rule in 1956. However, most academic sources do not take into account the ramifications of culture, class and gender as a contributing factor in domestic politics and the trajectory of nation-building, especially between the years of 1950s to the 1970s. Rather, this thesis assumes that domestic politics and nation building did not merely take place in the bubble of national interest but was influenced by the patrician class masculine values harboured by the strikingly homogenous first generation male political leaders. Their time at predominantly male-dominated institutions, both in the colony and the metropole, informed their outlook on the world and profoundly impacted the way they conceived an independent Singapore. By factoring these aspects into the equation, this thesis seeks to provide a much broader context of the actions and the reasoning for the decisions made by the individuals in power that shaped the political landscape and the trajectory of national development, underscoring the impact of such ideals on the social, political and economic fabric of the nation.